Fermentation of deproteinized cheese whey powder solutions to ethanol by engineered Saccharomyces cerevisiae : effect of supplementation with corn steep liquor and repeated-batch operation with biomass recycling by flocculation - Silva, Ana Carina (2010)
The lactose in cheese whey is an interesting substrate for the production of bulk commodities such as bio-ethanol, due to the large amounts of whey surplus generated globally. In this work, we studied the performance of a recombinant Saccharomyces cerevisiae strain expressing the lactose permease and intracellular ß-galactosidase from Kluyveromyces lactis in fermentations of deproteinized concentrated cheese whey powder solutions. Supplementation with 10 g/l of corn steep liquor significantly enhanced whey fermentation, resulting in the production of 7.4% (v/v) ethanol from 150 g/l initial lactose in shake-flask fermentations, with a corresponding productivity of 1.2 g/l/h. The flocculation capacity of the yeast strain enabled stable operation of a repeated-batch process in a 5.5-l air-lift bioreactor, with simple biomass recycling by sedimentation of the yeast flocs. During five consecutive batches, the average ethanol productivity was 0.65 g/l/h and ethanol accumulated up to 8% (v/v) with lactose-toethanol conversion yields over 80% of theoretical. Yeast viability (>97%) and plasmid retention (>84%) remained high throughout the operation, demonstrating the stability and robustness of the strain. In addition, the easy and inexpensive recycle of the yeast biomass for repeated utilization makes this process economically attractive for industrial implementation.